Assessing the Communication in Maintaining Quality and Timely Delivery of Project - Safaa Abd Ali Abdulameer, Mahmood Fahad Abd Ali, Kadhim Ahmed Jawad Abbas, (Opción, 2019)
This study measures the role of project manager’s communication skill for the maintenance time schedule and quality results of project. Regression analysis was carried out to assess the proposed framework. It is found that communication skill is critical for the success of project in term of timely delivery and maintaining quality of results. This study draws attention of project companies to take interest to develop communication skills of project managers. In conclusion, it is evident that communication plays an important role to complete the project activities on time. Consequently, quality of the project is also affected by project communication